2015
DOI: 10.1007/s00253-015-6498-0
|View full text |Cite|
|
Sign up to set email alerts
|

Lactic acid bacteria—20 years exploring their potential as live vectors for mucosal vaccination

Abstract: Lactic acid bacteria (LAB) are a diverse group of Gram-positive, nonsporulating, low G + C content bacteria. Many of them have been given generally regarded as safe status. Over the past two decades, intensive genetic and molecular research carried out on LAB, mainly Lactococcus lactis and some species of the Lactobacillus genus, has revealed new, potential biomedical LAB applications, including the use of LAB as adjuvants, immunostimulators, or therapeutic drug delivery systems, or as factories to produce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
98
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 93 publications
(111 reference statements)
1
98
0
1
Order By: Relevance
“…59 Since the early 1980s, gram-positive bacteria from the Bacillus or Lactococcus genera have been viewed as potential alternatives to E. coli for the production of recombinant proteins, their theoretical advantage being their capacity of secretion and relative adaptation to genetic manipulation. While there is an extensive literature on their use as expression systems, 60 and as live delivery vehicles for mucosal immunization, 61 data supporting their utility remains limited. Further investigation in this field is required.…”
Section: Bacteria: Between Evolution and Revolutionmentioning
confidence: 99%
“…59 Since the early 1980s, gram-positive bacteria from the Bacillus or Lactococcus genera have been viewed as potential alternatives to E. coli for the production of recombinant proteins, their theoretical advantage being their capacity of secretion and relative adaptation to genetic manipulation. While there is an extensive literature on their use as expression systems, 60 and as live delivery vehicles for mucosal immunization, 61 data supporting their utility remains limited. Further investigation in this field is required.…”
Section: Bacteria: Between Evolution and Revolutionmentioning
confidence: 99%
“…Lc. lactis was the first LAB species to have its whole genome sequenced, and there exists a wealth of genetic data on this species (8, 41, 42). In addition, Lc.…”
Section: Lactococcus Lactismentioning
confidence: 99%
“…Genetic modification technology has undergone considerable advances in recent years, and Lactococcus ( Lc .) lactis in particular has been established as an efficient expression system for recombinant proteins (RPs) (8) (Figure 1A). Thus, probiotics, which have excellent safety and health advantages, are likely to be very useful as producers of IBD therapeutic proteins and as agents for delivering such proteins to the GIT (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the use of the probiotic Lactobacillus as a vector delivery system has unmatched superiority compared to other known eukaryotes and prokaryotes (Wyszynska et al, 2015). In this research, using lactating porcine mammary tissue RNA as a template to obtain the N terminus pLF gene, we successfully obtained recombinant lactic acid bacteria expressing the pLF gene.…”
mentioning
confidence: 90%